"The Semantic and Linguistic Methodology of the Nasafis in the Interpreting Surah Al-Mulk: A Comparative Study." - Al-Rayahneh , Fadi Mahmoud; Awawdeh , Fatina Jamal (Journal of Ecohumanism, 2024)
Quranic interpretation has been a significant subject of scholarly debate throughout Islamic history, as we find that many interpreters, scholars, and enthusiasts have hurried to provide interpretations of the Quranic text. Among these prominent scholars who have greatly contributed to this field are Abu al-Barakat al-Nasafi and Abu Hafs al-Nasafi. Both scholars adopted distinctive methods in interpreting the Holy Quran, providing valuable insights into their understanding of the Quran’s message, values, beliefs, and legislation. Both emphasized rationality and logic in their interpretations, specifically of Surah Al-Mulk, aiming to reconcile religious teachings with philosophical ideas, using a special and organized approach that distinguishes each from the other: they may share methodological and stylistic points, yet in many aspects, their interpretative approaches differ, whether methodological or explanatory, all with the aim of reconciling the apparent contradictions within the religious text in their Nasafi style. This research addresses the following key topics: An introductory overview of "Abu al-Barakat al-Nasafi" and "Abu Hafs al-Nasafi", The methodologies of Abu al-Barakat al-Nasafi and Abu Hafs al-Nasafi in interpreting Surah Al-Mulk., Comparative analysis: similarities and differences in the interpretations of Surah Al-Mulk by Abu al-Barakat and Abu Hafs.